Evaluation of Community Based Disaster Preparedness Training for UGM Health Study Program Students in 2016 - Istianto Kuntjoro; Mora Claramita; Wahyudi Istiono (Faculty of Medicine, Public Health, and Nursing, 2019)
Background: Disasters are events that destroy infrastructure, take casualties, disrupt life and systems, damage social order, health, and security, and occur on a global scale. Various places in the world began to include disaster management in their doctors' education curricula, including Indonesia, which is geologically located in areas with high potential for disasters, which have the potential to be continually harmed by disasters that always occur.Objective: To see whether the disaster management training in UGM semester 7 study program students have properly increased the students' knowledge and attitude towards disaster.Method: Quantitative research design and using Quasi-experimental method, without control, with pre-test and post-test instruments. The population of this study was students of medical education study programs, nutrition study program students, and nursing study students, with a sample of 175 students. The independent variable measured is community-based disaster management training. Collecting research data using an instrument in the form of a questionnaire after that was analyzed by a paired T-test.Results: There was an increase in the score of knowledge and attitudes about disaster after receiving training, but the achievement of the mean value of each question was still close to the median. The highest increase in scores achieved in each study program is a value of 6.Conclusion: There was an increase in knowledge about disasters and disaster preparedness attitudes in 2016 health study program students who attended Disaster Preparedness training.